2014
DOI: 10.1515/cmam-2014-0005
|View full text |Cite
|
Sign up to set email alerts
|

Functional A Posteriori Error Estimation for Stationary Reaction-Convection-Diffusion Problems

Abstract: -A functional type a posteriori error estimator for the finite element discretization of the stationary reaction-convection-diffusion equation is derived. In case of dominant convection, the solution for this class of problems typically exhibits boundary layers and shock-front like areas with steep gradients. This renders the accurate numerical solution very demanding and appropriate techniques for the adaptive resolution of regions with large approximation errors are crucial. Functional error estimators as de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…As a side result, we also prove in Proposition 5.1 that the weights w K in (1.11) are necessary for robustness of any equilibrated flux estimate involving the terms ε∇u T + ε −1 σ T K whenever σ T is a piecewise polynomial on T (and thus its construction does not involve any submesh), regardless of the precise details of the construction of σ T . This proves that several flux equilibrations proposed in the past cannot be robust with respect to reaction dominance in general (although in many constellations, no loss of robustness may be numerically observed), including those of Repin and Sauter [29], Ainsworth et al [1], Eigel and Samrowski [16], Eigel and Merdon [15], and Vejchodský [32,34,33].…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…As a side result, we also prove in Proposition 5.1 that the weights w K in (1.11) are necessary for robustness of any equilibrated flux estimate involving the terms ε∇u T + ε −1 σ T K whenever σ T is a piecewise polynomial on T (and thus its construction does not involve any submesh), regardless of the precise details of the construction of σ T . This proves that several flux equilibrations proposed in the past cannot be robust with respect to reaction dominance in general (although in many constellations, no loss of robustness may be numerically observed), including those of Repin and Sauter [29], Ainsworth et al [1], Eigel and Samrowski [16], Eigel and Merdon [15], and Vejchodský [32,34,33].…”
Section: Introductionmentioning
confidence: 78%
“…It is then seen that the inclusion of the weight term w K in Theorem 3.1 is necessary when considering flux equilibrations from vector-valued piecewise polynomial subspaces of H(div, Ω) on the mesh T , regardless of the precise details of the construction of the flux. Examples of flux equilibrations proposed in the past that cannot be robust in general include Repin and Sauter [29], Ainsworth et al [1], Eigel and Samrowski [16], Eigel and Merdon [15], and Vejchodský [32,33,34]. We now present an example of a situation where (5.3) holds and where κh/ε can be arbitrarily large.…”
Section: Necessity Of the Weights W Kmentioning
confidence: 94%
“…Most work on functional type a posteriori error control for the reaction-convection-diffusion problem has concentrated on error estimation for approximations of the primal variable. The error estimates resulting from this research can be found in [4,5,8,9], and some of these results are also exposed in the book [10]. In [8] the authors also derive two-sided estimates for mixed approximations in combined norms.…”
Section: Introductionmentioning
confidence: 89%
“…It is worth mentioning the latest work [32] of Tobiska and Verfürth, where the robust error estimation is extended to other stabilized finite element methods. There are also other proposals in the literature for estimating the error with respect to a priori given (sometimes mesh-dependent) norm, such as residual error indicators [3,23], hierarchical estimates [1], averaging techniques [10] or functional (constant-free) error estimates [13]. All the works mentioned above are only limited to the conforming methods where the discrete solution space is in the primary space.…”
Section: Introductionmentioning
confidence: 99%